Understanding the Underlying Stakes of Insecurity and Popular Vindictiveness: A Case Study of the Anosy Region - Tsimiondreke Mahasoa; Etienne Stefano Raherimalala; Ranjatson Jean Patrick; Andrianjary Myriam; Fidelio Arnold Ulrich; Ratiarimananjatovo Narindra; Robijaona Rahelivololoniaina Baholy (Matondang Journal, 2024)
Beyond the widespread judicial laxity, the failure of the security system in rural areas, and popular frustration, this article aims to examine the underlying issues of the two chronic social phenomena in the Anosy region, focusing on the case of Amboasary Sud: cattle theft and mob justice. The question then arises: what are the cultural and economic factors that influence cattle theft and mob justice? In this regard, primarily qualitative data from documents, field observations, and interviews were collected and analyzed. Following an analysis from a systemic perspective, our results reveal two main aspects. Firstly, the phenomena of cattle theft and mob justice, being interdependent, require an in-depth exploration of their cultural dimension. Culture thus plays a dual role: on one hand, it amplifies cattle theft, as the Bara community in Amboasary Sud inherits a civilization where theft symbolizes strength, perseverance, and constitutes a rite of passage into adulthood. On the other hand, culture can be considered an essential element in resolving conflicts related to cattle theft and mob justice, as it encompasses various values, representations, and social norms that rationalize the actions of both thieves and victims. Secondly, our results underscore the need to reconsider economic factors as primary drivers of the proliferation of these two phenomena. Given the persistent poverty, environmental problems such as drought and chronic malnutrition in the south, particularly in Amboasary Sud, addressing economic and environmental issues can significantly improve the situation.